If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = 24x + 2 Reorder the terms: 2y = 2 + 24x Solving 2y = 2 + 24x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 1 + 12x Simplifying y = 1 + 12x
| -4(2y-8)-y=-3(y-3) | | 5/6z=5/8 | | x^2-4x+64=0 | | (-a-7b+3)6ab= | | 25x+-6x+120=21x | | ax-7b=4c | | 2x-5(4x+10)=58 | | (3x-4)(3x-4)+16=0 | | (x-8)(x-8)-81=0 | | y/5+y/4=7/5 | | -4(6y-5)-y=-3(y-2) | | 4k^2+12K-9=0 | | 1/5x+1/4=-2 | | 5/12X=3 | | 3/8X=24 | | 1/2X=11 | | 36r*5= | | -2y-7(6y-8)=1+9(1-y) | | E=LR+Lr | | 4/9X=20/18 | | r+6=3(r-3) | | x^3=29 | | 4/9X=10/18 | | 6r*5= | | 2r+6=3(3-r) | | 25v^2-64f^2=0 | | 5/7X=10/2 | | 6/12x=4/3 | | 10=-3x-17 | | 2/3x=5/6 | | 2s^2+15s+27=0 | | 5.07x=344.76 |